eCM 2010
DOI: 10.22203/ecm.v020a26
|View full text |Cite
|
Sign up to set email alerts
|

An RGD-restricted substrate interface is sufficient for the adhesion, growth and cartilage forming capacity of human chondrocytes

Abstract: This study aimed at testing whether an RGD-restricted substrate interface is sufficient for adhesion and growth of human articular chondrocytes (HAC), and whether it enhances their post expansion chondrogenic capacity. HAC/ substrate interaction was restricted to RGD by modifying tissue culture polystyrene (TCPS) with a poly(ethylene glycol) (PEG) based copolymer system that renders the surface resistant to protein adsorption while at the same time presenting the bioactive RGD-containing peptide GCRGYGRGDSPG (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 61 publications
2
26
0
1
Order By: Relevance
“…31 Similarly, chondrocyte spreading due to high RGD concentration has shown to decrease cell size and reduce ECM synthesis overtime in polyethylene glycol dimethacrylate (PEGDM) hydrogel. 32,33 Accordingly, in our study, slight decrease in GAG and collagen accumulation was observed in PEG-RGD hydrogel compared with that in PEG-RDG hydrogels. Conversely, ECM-based hydrogels exhibited biodegradation properties upon exposure to their respective degradable enzymes.…”
Section: Discussionsupporting
confidence: 51%
“…31 Similarly, chondrocyte spreading due to high RGD concentration has shown to decrease cell size and reduce ECM synthesis overtime in polyethylene glycol dimethacrylate (PEGDM) hydrogel. 32,33 Accordingly, in our study, slight decrease in GAG and collagen accumulation was observed in PEG-RGD hydrogel compared with that in PEG-RDG hydrogels. Conversely, ECM-based hydrogels exhibited biodegradation properties upon exposure to their respective degradable enzymes.…”
Section: Discussionsupporting
confidence: 51%
“…4C) are similar to a previous 2-D study. It found that higher RGD concentrations led to an initial increase in chondrocyte spreading followed by a decrease in the chondrocyte foot-print over time and an increase of initial spreading over the control but leads to decreased cell size over time [27]. The organization of actin within chondrocytes is also thought to contribute to cellular phenotype, pericellular matrix synthesis and retention of the proteoglycans in the tissue [62,72].…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the following are combinations thereof (i.e. [142][143][144][145][146][147][148][149][150][151][152][153][154][155] At pH 7.4 (HEPES 156 or PBS buffer), these PLL-g-PEG macromolecules were shown to display the ability to spontaneously self-assemble onto a variety of metal oxide substrates made of niobium, [142][143][144]151,152,154,155 titanium, 142,143,[145][146][147][148]150,153 silicon/titanium, 142 or tantalum. Nonetheless, these 'outliers' are no less important and form, as a matter of fact, some of the best antifouling coatings known against blood plasma/serum (see Table 1 in upcoming subsection IV.A.).…”
Section: Iie Hybrid Derivative and Bioinspired Materialsmentioning
confidence: 99%